Characterization of a collection of perennial Panicum species - Wouw, M. van de; Jorge, M.A.B.; Bierwirth, J.; Hanson, Jean (2008)
A collection of 74 perennial Panicum accessions, belonging to 6 different species, maintained at the field genebank of the International Livestock Research Institute, was described using 49 agromorphological characters in a multivariate analysis.